2012
DOI: 10.1016/s0034-7094(12)70123-x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Noise Pollution in Anesthesiology

Abstract: The results of the main articles in literature on the subject are discussed, concerning the sources of noise pollution and its effects on workers, particularly the anesthesiologist. Emphasis is given to legislation and recommendations to minimize the effects caused by noise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Noise may be described as aperiodic acoustic signals originated from the overlap of several vibration movements with different, unrelated frequencies 1 . Noise has been increasing over the years, specifically in large metropolitan areas.…”
Section: Introductionmentioning
confidence: 99%
“…Noise may be described as aperiodic acoustic signals originated from the overlap of several vibration movements with different, unrelated frequencies 1 . Noise has been increasing over the years, specifically in large metropolitan areas.…”
Section: Introductionmentioning
confidence: 99%
“…As the use of ear protector might not be suitable as it could hinder communication and is generally regarded as cumbersome; minimizing the noise levels might be the best option. This can be achieved by applying a noise barrier around or near the operating table, isolating the source of noise, increasing the absorption of walls and ceilings, and decreasing the time exposure of health professionals in operating theatre [6]. After all, the most preventive measures to prevent NIHL are the use of hearing protective devices, if it is not possible; some engineering intervention should be implemented [7].…”
Section: Resultsmentioning
confidence: 99%
“…Although the noise levels in the OR may not be high enough to require ear protection, the noise in an OR does have other effects related to patient safety (eg, communication interference, increased stress levels) 9 . Although the levels reported in the NIOSH study were below levels determined by NIOSH to create hearing loss, the authors concluded the levels were high enough to possibly cause interference with communication 2 .…”
Section: Noise In the Ormentioning
confidence: 97%